Fast and furious: Early differences in growth rate drive short-term plant dominance and exclusion under eutrophication - Zhang, P; Hefting, MM; Soons, MB; Hector, A; Turnbull, LA; et al. (Wiley, 2020)
The reduction of plant diversity following eutrophication threatens many ecosystems worldwide. Yet, the mechanisms by which species are lost following nutrient enrichment are still not completely understood, nor are the details of when such mechanisms act during the growing season, which hampers understanding and the development of mitigation strategies. Using a common garden competition experiment, we found that early‐season differences in growth rates among five perennial grass species measured in monoculture predicted short‐term competitive dominance in pairwise combinations and that the proportion of variance explained was particularly greater under a fertilization treatment. We also examined the role of early‐season growth rate in determining the outcome of competition along an experimental nutrient gradient in an alpine meadow. Early differences in growth rate between species predicted short‐term competitive dominance under both ambient and fertilized conditions and competitive exclusion under fertilized conditions. The results of these two studies suggest that plant species growing faster during the early stage of the growing season gain a competitive advantage over species that initially grow more slowly, and that this advantage is magnified under fertilization. This finding is consistent with the theory of asymmetric competition for light in which fast‐growing species can intercept incident light and hence outcompete and exclude slower‐growing (and hence shorter) species. We predict that the current chronic nutrient inputs into many terrestrial ecosystems worldwide will reduce plant diversity and maintain a low biodiversity state by continuously favoring fast‐growing species. Biodiversity management strategies should focus on controlling nutrient inputs and reducing the growth of fast‐growing species early in the season.